Mn Incorporation in Large Benthic Foraminifera: Differences Between Species and the Impact of pCO2 - van Dijk, Inge; de Nooijer, Lennart J.; Barras, Christine; Reichart, Gert-Jan (Frontiers in Earth Science, 2020)
Element concentrations of calcite precipitated by foraminifera reflect chemical and physical properties of seawater and can therefore be used to reconstruct (paleo-)environmental conditions. Foraminiferal carbonate associated manganese incorporation (expressed here as Mn/Ca) is a potential proxy for seawater oxygenation, although the impacts of other environmental parameters need to be quantified before Mn/Ca can be robustly applied. Here we report the isolated impact of seawater carbonate chemistry on manganese incorporation in the shells of two large symbiont-bearing benthic foraminiferal species. Moreover, we investigated the role of biomineralization on manganese incorporation by using species with contrasting calcification pathways: the hyaline species Amphistegina gibbosa and the porcelaneous species Sorites marginalis. Furthermore, analyzing shells from a wide range of species grown under identical conditions allowed assessment of species-specific Mn incorporation in other foraminiferal species. Our observations show that species specific differences in biomineralization strategies are the dominant factor determining Mn content. Shells from porcelaneous species, with relatively high Mg contents, are generally also enriched in Mn compared to low-Mg/Ca foraminifera. Superimposed on the effect of biomineralization, chemical speciation of elements in seawater as a function of pCO2 also affects their incorporation. Whereas the impact of the carbonate system is limited, the inter-specific differences call for species specific calibrations in order to use Mn uptake as a (paleo-)oxygenation proxy.